Conjunctions Found in Short Story “Mr. and Mrs. Elliot” - I Made Sutasoma; I Gusti Bagus Wahyu Nugraha Putra; I Komang Sulatra (Austronesian: Journal of Language Science & Literature, 2022)
A conjunction is a word used to link or connect sentences or clauses to another to make the words readable and easy to understand. This study aims to determine how many types of conjunction appeared in a short story entitled “Mr. and Mrs. Elliot.” The qualitative method was applied to collect and analyze the data source. The researchers used the theory from Halliday and Hassan (1976) to analyze types of a conjunction such as Additive, Adversative, Causal, and Temporal. In collecting the data, researchers used the observation method. Several steps were used, such as reading, collecting, and classifying the data based on the types of conjunction. As a result, the researchers found there are 27 or (57,4%) data of Additive Relation expressed by a conjunction and, or, 6 data or (12,7%) of Adversative Relation expressed by conjunction but 1 data or (2,1%) of Causal Relation expressed by conjunction so, and 13 data or (27,6%) Temporal Relation expressed by conjunction after, before, and when.